2021
DOI: 10.1177/1753193420983719
|View full text |Cite
|
Sign up to set email alerts
|

Developing a core outcome set for hand fractures and joint injuries in adults: a systematic review

Abstract: This study identifies the treatment outcome domains used in recently published studies on the treatment of hand fractures and joint injuries with the aim to inform development of a core outcome set. Seven databases were searched from January 2014 to March 2019 for randomized and quasi-randomized studies and large prospective observational studies. We identified 1777 verbatim outcomes in 160 eligible studies. From the verbatim outcomes we distinguished 639 unique outcomes, which we categorized into 74 outcome d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These ranged across 74 WHO ICF outcome domains. 16 The qualitative study developed 35 outcome domains across six broad themes. The two sets of domains were synthesized by the research group to form a longlist of 37 outcome domains, with linking of outcome domains as shown in Supplementary Material table i.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These ranged across 74 WHO ICF outcome domains. 16 The qualitative study developed 35 outcome domains across six broad themes. The two sets of domains were synthesized by the research group to form a longlist of 37 outcome domains, with linking of outcome domains as shown in Supplementary Material table i.…”
Section: Resultsmentioning
confidence: 99%
“…Phase 1: outcome identification. A systematic review of published clinical research over a five-year period from 2014 to 2019 was conducted, 16 as per the protocol registered on PROSPERO (CRD42019126299), with outcomes extracted verbatim. In brief, we extracted unique outcomes from recently published clinical studies on management of hand fractures and joint injuries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future COS development studies may consider the approach suggested by Dwan et al 59 to assess outcome reporting bias in reviews. Other COS developers reviewing primary studies of hand 60 and cancer surgery 61 have explored this and found a high risk of outcome reporting bias. We did not determine the overlap of primary studies across included reviews, and this may have influenced the number of duplicate outcomes in the list.…”
Section: Discussionmentioning
confidence: 99%